Effect of hydrocolloid on characteristics of gluten free bread from rice flour and fermented cassava flour (Fercaf) - Dianika Lestari; Made Tri Ari Penia Kresnowati; Afina Rahmani; Lienda Aliwarga; Yasid Bindar (Reaktor, 2019)
Gluten free (GF) bread was made from rice flour and fermented cassava flour. Fermented cassava flour (FERCAF) was produced using a specific design of closed and circulated fermenter, which resulted on a white and neutral aroma flour. However, FERCAF did not have structural component (such as gluten) to provide dough's viscoelasticity and ability to retain gas to hold the volume of bread after baking. Hydrocolloids were added to FERCAF based GF bread to increase water binding of dough. This research aimed to investigate the effect hydrocolloids addition on the characteristics of GF bread made from rice flour and fermented cassava flour (FERCAF). Effect of hydrocolloids to flour ratio (2 %, 3 % and 5 %-wt) and types of hydrocolloid (xanthan gum, agar, and carrageenan) on specific volume of bread, bake loss, bread texture, and microstructure of the bread were investigated. Bread textures were measured using Texture Profile Analyzer (TPA), and microstructure was analysed by SEM. Data experiment showed that addition of hydrocolloids improved GF bread characteristics, specifically increased volume specific, increased porosity, and reduced hardness of GF bread.Keywords: gluten-free bread; cassava; fermented cassava flour; Fercaf; hydrocolloids